Polycystic Ovary Syndrome: Effect and Mechanisms of Acupuncture for Ovulation Induction. (2nd September 2013) - Johansson, Julia; Stener-Victorin, Elisabet
Abstract : Polycystic ovary syndrome (PCOS), the most common endocrine disorder among women of reproductive age, is characterized by the coexistence of hyperandrogenism, ovulatory dysfunction, and polycystic ovaries (PCO). PCOS also represents the largest part of female oligoovulatory infertility, and the management of ovulatory and menstrual dysfunction, comprises a third of the high costs of PCOS treatment. Current pharmacological and surgical treatments for reproductive symptoms are effective, however, associated with negative side effects, such as cardiovascular complications and multiple pregnancies. For menstrual irregularities and ovulation induction in women with PCOS, acupuncture has indicated beneficial effects. This review will focus on the results from randomized controlled acupuncture trials for regulation of menstrual dysfunction and for inducing ovulation in women with PCOS although there are uncontrolled trials with nonetheless interesting results. Animal experimental studies will be further discussed when they can provide a more mechanistic explanatory view.